Adhesion Study in Metal-ceramic Systems of Dental Restoration by Acoustic Emission. (2015) - Ortega, Valeria I.; Pumarega, María Isabel López; Nieva, Nicolás; Gomez, Martin P.; Kaplan, Andrea; Docimo, Leandro
Abstract: This study analyzes and quantifies the adhesion strength at interfaces between a metal and other ceramic materials. This is part of a larger work focused on the characterization of this type of interfaces applied in the area of dental materials. The experimental work consists in preparation, manufacturing and testing of specimens under IRAM-ISO 9693 Standard Project, related with porcelain-metal dental restoration systems. The Standard proposes assays involving the determination of the applied force causing the detachment or separation of a portion of ceramic deposited on a metal base, during a three-point bending test. Nowadays, there are no precise methods to assess with accuracy the instant of the debonding. It is a continuation of a previous work, using the Acoustic Emission (AE) method to determine more precisely the process of separation between the materials and also to assess the type of fracture process. This technique involves detection of signals produced by any source of AE such as propagation of microcracks, deformation, etc. These sources change the material stress field, producing and propagating elastic waves that reach the surface, where they are detected by the AE sensors. In these tests, the bending load is applied at a constant rate on the metal substrate. A load cell senses the applied force. The AE is measured with a two-channel AE system, obtaining the features of the AE signals. Furthermore, a displacement sensor (LVDT) was implemented to correlate load with the tip displacement. The tests are monitored and filmed with a digital microscope.